FOOD DELIVERY SERVICE AND ITS ASSOCIATION WITH ANTHROPOMETRIC MEASUREMENTS AMONG UNDERGRADUATE FEMALE STUDENTS IN IIUM KUANTAN - MOKHTAZAR, INTAN SYUHADA; HAMIRUDIN, ALIZA HASLINDA (International Journal of Allied Health Sciences, 2020)
Introduction: Food delivery system allows customers to quickly and easily retrieve online menus which customers can search or browse and place and order with just several clicks using their phone or other devices. The accessibility of unhealthy food through this service can further contribute to obesity which is considered as a major health problem. Aim: To identify the use of food delivery service among undergraduate female students in International Islamic University Malaysia (IIUM), Kuantan and its association with anthropometric measurements. Methods: A cross-sectional study was carried out involving 113 undergraduate female students aged between 18 and 25 years in IIUM, Kuantan campus. Respondents were selected based on convenience sampling. Respondents were required to fill in a set of questionnaires containing 2 parts; demographic characteristics and food delivery service. Body weight, height and waist circumference were measured by the researcher. All data for anthropometric measurements were collected using a stadiometer, portable weight scale and measuring tape. Results: The results showed that the main factor of using food delivery service at the mahallahs (hostels) was because of ease and convenience. Most of the students (75.2%) bought fast food using food delivery service. Findings showed no significant association between the frequency of food delivery service and body mass index (BMI) (p=0.24). There was a significant association between the frequency of food delivery service and waist circumference (p=0.039). Conclusions: Food delivery service is majorly used by the undergraduate female students due to its accessibility and it was associated with waist circumference. For future research, it is recommended to include males as study respondents, as well as frequency of fast food dine-in and delivery service. KEYWORDS: Obesity, Body mass index, Waist circumference, Food delivery service